Hepatic Macrophage Types Cluster with Disease Etiology in Chronic Liver Disease and Differ Compared to Normal Liver: Implications for Their Biologic and Diagnostic Role. (May 2023) - Zhang, Xiaoming; Thompkins-Johns, Alexandra; Ziober, Amy; Zhang, Paul J; Furth, Emma E.
Introduction. Macrophages are phenotypically heterogeneous cells that play a vital role in hepatic fibrogenesis. We aimed to compare the macrophage profiles between normal livers and those with various chronic liver diseases in the precirrhotic fibrosis stage. Methods. Immunohistochemistry was performed for three macrophage markers (CD163, CD68, and IBA1) on 48 liver biopsies. Digital image analysis and automated cell count were used to calculate the densities of immunostained cells in two selected regions of interest: the periportal region and the perivenous region. Results. The absolute and relative densities of the macrophage phenotypes in relationship with zones and etiologies showed four distinct patterns by hierarchical cluster analysis: (1) no significant increase in the macrophage densities in either periportal or perivenous regions - nonalcoholic steatohepatitis; (2) significant increase in the selected macrophage densities in both periportal and perivenous regions - Hepatitis C; (3) significant increase in the macrophage densities only in periportal region - alcoholic liver disease, primary sclerosing cholangitis, and primary biliary cholangitis; and (4) significant increase in the densities of all types of macrophages in both periportal and perivenous regions - autoimmune hepatitis. Conclusions. There are distinct macrophage phenotypic and zonal geographic signatures correlating to etiologies of chronic liver disease in the precirrhotic stage.